Answer:
1. x< 3
2. x>12
have a great day :)
Step-by-step explanation:
<span><span> p9/p3</span> </span>Final result :<span> p6
</span>Reformatting the input :
Changes made to your input should not affect the solution:
(1): "p3" was replaced by "p^3". 1 more similar replacement(s).
Step by step solution :<span>Step 1 :</span><span> p9
Simplify ——
p3
</span>Dividing exponential expressions :
<span> 1.1 </span> <span> p9</span> divided by <span>p3 = p(9 - 3) = p6</span>
Final result :<span> p<span>6</span></span>
5 5/9
5 * 5/9
25/9
The correct answer is 25/9, as shown above.
Answer:
a = 2(vt -d)/t^2
Step-by-step explanation:
Add the term containing "a":
d + a(t^2/2) = vt
Subtract d:
a(t^2/2) = vt -d
Multiply by the inverse of the coefficient of "a":
a = 2(vt -d)/t^2